2013
DOI: 10.1039/c3tc30805g
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of rhodium substituted ε-iron oxide exhibiting super high frequency natural resonance

Abstract: In this study, we demonstrate a synthesis of rhodium substituted 3-iron oxide, 3-Rh x Fe 2Àx O 3 (0 # x # 0.19), nanoparticles in silica. The synthesis features a sol-gel method to coat the metal hydroxide sol containing Fe 3+ and Rh 3+ ions with a silica sol via hydrolysis of alkoxysilane to form a composite gel. The obtained samples are barrel-shaped nanoparticles with average long-and short-axial lengths of approximately 30 nm and 20 nm, respectively. The crystallographic structure study using X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Several studies have demonstrated the modulation of the resonance frequency depending on different elements substituted in the crystalline structure of the 3-Fe 2 O 3 phase. [5][6][7][8] Specially in thin lm form, this polymorph shows a ferromagnetic and ferroelectric response. Thus it opens the possibility of using it as a room temperature multiferroic in a real device.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the modulation of the resonance frequency depending on different elements substituted in the crystalline structure of the 3-Fe 2 O 3 phase. [5][6][7][8] Specially in thin lm form, this polymorph shows a ferromagnetic and ferroelectric response. Thus it opens the possibility of using it as a room temperature multiferroic in a real device.…”
Section: Introductionmentioning
confidence: 99%
“…This synthetic route differs from our previously reported methods. [27,28] Rhodium nitrate (0.9 mmol (1), 1.2 mmol (2)) and iron oxide hydroxide (28.9 mmol (1), 25.6 mmol (2)) were DOI: 10.1002/adpr.202100319…”
Section: Methodsmentioning
confidence: 99%
“…These particle sizes are smaller than those previously synthesized by the sol-gel method, d ¼ 19-32 nm. [28] Powder X-ray diffraction (XRD) patterns were measured using a Rigaku Ultima IV (Cu Kα source, λ ¼ 1.5418 Å) (Figure 1c and S1, Table S1, Supporting Information). 1 consisted of 93 wt% of ε-iron oxide (orthorhombic, Pna2 1 ) and 7 wt% of α-iron oxide (rhombohedral, R3c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable attention has been given to the absorbing materials in the filed of anti-EM interference coatings and self-concealing technology [4,5]. The microwave absorber is considered as a specially designed material in order to suppress the reflected electromagnetic energy incident on the surface of the absorber by dissipating the magnetic and/or electrical fields of the wave into heat [6].…”
Section: Introductionmentioning
confidence: 99%